Malaysia plan of action for people with disabilities 2016-2022: way forward - Abdul Rahim, Asiah; Abd Samad, Nur Amirah; Said, Ismail; W Seman, Wan Mohamad Amin (2017)
The objective of this paper, firstly to identify the commitment of Malaysia government towards providing good facilities, education, health, accessibility, culture, social attraction for People with Disabilities (PwDs) in society. Secondly, to review various approaches and strategies applied by the government and non-government to fulfil the intention of Malaysian Plan of Action for People with Disabilities 2016-2022. Malaysian has sign up Convention of Human Right in 2006 and have agreed to adopt and enact laws so that persons with disabilities would have equal rights to education, employment, and cultural life; the right to own and inherit property; not be discriminated against in marriage, children; not be unwilling subjects in medical experiments. Universal Design and Social Responsibility are tightly related in term of its core subjects such as Human Rights against discrimination and specific vulnerable groups; economic, social and cultural rights; consumer issues such as access to essential services; education, awareness and community involvement as well as technology development and access; and social investment. Social Responsibility is an ethical ideology or theory than an entity, be it an organization or individual, has an obligation to act to benefit society at large and universal design is an active agent in this process. The methodology applied for this paper by using table research and as well as secondary data based on literature review. The data will be analysed using content analysis and case studies. The contribution of this paper will give Malaysian opportunities to share their experiences with other nations on how Malaysian implementing action of plan for People with Disabilities (PwDs) for the future in relation to human rights.